First record of Pulvinaria urbicola Cockerell (Hemiptera: Coccidae) from India, with a key to the Indian species of Pulvinaria Targioni Tozzetti - Joshi, Sunil (Zootaxa, 2017)
The notoriously destructive and invasive soft scale, Pulvinaria urbicola Cockerell (Hemiptera: Coccidae), is recorded for the first time from India. This scale, with variable morphological appearance and similarities with other known scales of the same genus established in India, is redescribed to facilitate its identification and separation from other similar species. Information on its host range, natural enemies and distribution is provided. Management options in the event of an outbreak are discussed briefly. A key to the species of Pulvinaria Targioni Tozzetti in India is also provided. This new arrival warrants special attention in India as it is a potentially damaging plant pest and has a broad host range across many plant families.